Directed Dedifferentiation Using Partial Reprogramming Induces Invasive Phenotype in Melanoma Cells. (19th January 2016) - Knappe, Nathalie; Novak, Daniel; Weina, Kasia; Bernhardt, Mathias; Reith, Maike; Larribere, Lionel; Hölzel, Michael; Tüting, Thomas; Gebhardt, Christoffer; Umansky, Viktor; Utikal, Jochen
Abstract: The combination of cancer-focused studies and research related to nuclear reprogramming has gained increasing importance since both processes—reprogramming towards pluripotency and malignant transformation—share essential features. Studies have revealed that incomplete reprogramming of somatic cells leads to malignant transformation indicating that epigenetic regulation associated with iPSC generation can drive cancer development [J Mol Cell Biol 2011;341–350; Cell 2012;151:1617–1632; Cell 2014;156:663–677]. However, so far it is unclear whether incomplete reprogramming also affects cancer cells and their function. In the context of melanoma, dedifferentiation correlates to therapy resistance in mouse studies and has been documented in melanoma patients [Nature 2012;490:412–416; Clin Cancer Res 2014;20:2498–2499]. Therefore, we sought to investigate directed dedifferentiation using incomplete reprogramming of melanoma cells. Using a murine model we investigated the effects of partial reprogramming on the cellular plasticity of melanoma cells. We demonstrate for the first time that induced partial reprogramming results in a reversible phenotype switch in melanoma cells. Partially reprogrammed cells at day 12 after transgene induction display elevated invasive potential in vitro and increased lung colonization in vivo. Additionally, using global gene expression analysis of partially reprogrammed cells, we identified SNAI3 as a novel invasion-related marker in human melanoma. SNAI3 expression correlates with tumor thickness in primary melanomas and thus, may be of prognostic value. In summary, we show that investigating intermediate states during the process of reprogramming melanoma cells can reveal novel insights into the pathogenesis of melanoma progression. We propose that deeper analysis of partially reprogrammed melanoma cells may contribute to identification of yet unknown signaling pathways that can drive melanoma progression. Abstract : Using mouse studies it has been shown that partial reprogramming of somatic cells leads to reversible hyperplasia and malignant transformation in vivo without the acquisition of genetic mutations (Ohnishi et al., 2014). In our study we proved that partial reprogramming turns murine melanoma cells into highly invasive cancer cells with increased metastatic potential, indicating that nongenetic influences (i.e., reprogramming) can not only affect initiation but also progression of tumor development. We used this system to identify a novel progression-related marker in human melanoma.